Просторот на другоста во „Сталкер“ на Андреј Тарковски - Трајче Стамески (My University, 2017)
The spaces of otherness in Stalker by Andrei Tarkovsky This text represents a hermeneutic and phenomenological interpretation of the concepts of the mysterious room and the intellectual skepticism in the cult movie by Andrei Tarkovsky. We take a look at the paradigmatic topos of the mysterious room from a historical perspective from the myth, folk literature, up to the contemporary European texts, as well as the way this concept hybridizes with the obvious skepticism of the intellectual in the film of Tarkovsky. The key elements of the thesis in this text are based on the interdisciplinary relations between literature and film, as well as the philosophical dialectics of Hegel, according to which in every society and culture there are many contradictions and tensions such as: intellect and faith, prison and freedom, subjectivity and authority. With the constitution of a complex, contradictory and fantastic Zone, this film by Andrei Tarkovsky can also be perceived as an allegory of human consciousness, the need for faith in a rational world, in which both ugly and unpleasant dreams and desires equally exist in the hearts of the people.
Keywords: Literature, film, Interdisciplinarity, Stalker, Zona